Study of Additive Dither on Restraining Signal Truncation Error - Tao Liu; Shulin Tian; Zhigang Wang; Lianping Guo (Institute of Advanced Engineering and Science, 2014)
Owing to the limited calculation precision during digital signal processing, the intermediate stages’ signal-bit-width truncation should be executed to realize the conversion from high precision to low one. As method of direct truncation will degenerate the Spurious Free Dynamic Range (SFDR) performance of the output signal, this paper proposed that additional digital dither should be added before operation of truncation, which could decline the harmonic distortion efficiently and extend the dynamic range of the truncated signal significantly. Two simulations for truncation operation towards signal with additive Gaussian dither and uniform dither are carried out to prove the validity of the proposed method. Comparative studies demonstrate that the proposed algorithm applied in Gaussian dithering and uniform dithering could improve the output SFDR performance by about 16dB and 15dB respectively.